A nuclear lamina‐chromatin‐Ran GTPase axis modulates nuclear import and DNA damage signaling. Issue 1 (19th December 2018) - Dworak, Natalia; Makosa, Dawid; Chatterjee, Mandovi; Jividen, Kasey; Yang, Chun‐Song; Snow, Chelsi; Simke, William C.; Johnson, Isaac G.; Kelley, Joshua B.; Paschal, Bryce M.
Abstract: The Ran GTPase regulates nuclear import and export by controlling the assembly state of transport complexes. This involves the direct action of RanGTP, which is generated in the nucleus by the chromatin‐associated nucleotide exchange factor, RCC1. Ran interactions with RCC1 contribute to formation of a nuclear:cytoplasmic (N:C) Ran protein gradient in interphase cells. In previous work, we showed that the Ran protein gradient is disrupted in fibroblasts from Hutchinson–Gilford progeria syndrome (HGPS) patients. The Ran gradient disruption in these cells is caused by nuclear membrane association of a mutant form of Lamin A, which induces a global reduction in heterochromatin marked with Histone H3K9me3 and Histone H3K27me3. Here, we have tested the hypothesis that heterochromatin controls the Ran gradient. Chemical inhibition and depletion of the histone methyltransferases (HMTs) G9a and GLP in normal human fibroblasts reduced heterochromatin levels and caused disruption of the Ran gradient, comparable to that observed previously in HGPS fibroblasts. HMT inhibition caused a defect in nuclear localization of TPR, a high molecular weight protein that, owing to its large size, displays a Ran‐dependent import defect in HGPS. We reasoned that pathways dependent on nuclear import of large proteins might be compromised in HGPS. We found that nuclear import of ATM requires the Ran gradient, and disruption of the Ran gradient in HGPS causes a defect in generating nuclear γ‐H2AX in response to ionizing radiation. Our data suggest a lamina–chromatin–Ran axis is important for nuclear transport regulation and contributes to the DNA damage response.